IMPLEMENTATION OF INTEGRATED SCIENCE INSTRUCTION ASSESSMENT AS AN ALTERNATIVE TO MEASURE SCIENCE PROCESS SKILLS AND SOCIAL ATTITUDES - Sukardiyono Sukardiyono; Dadan Rosana (Universitas Negeri Yogyakarta, 2017)
Curriculum 2013 requires a paradigm shift in the teachers manage learning, including assessment. Research on the implementation of integrated science instruction assessmentis an attempt to overcome the problems in science learning assessment in Junior High School. Rate the former tend to simply measure cognitive ability, so that teachers rarely pay attention to ratings on science process skills of students and social attitudes. This research aims to; (1) produce integrated science assessment practical instruction through the feasibility test in science learning class (2) to get the measure of science process skills and social attitudes of learners using instruments developed. This research is a development that adapt the model Borg and Gall (1983). Aiken's Formula V is used to analyze the instrument by the validator. This research resulted in: (1) integrated science instruction assessment practical through feasibility testing in the classroom science lessons with the following characteristics: (a) the observation sheet form checklist used by teachers to observe the science process skills of learners is only at the stage of observing, measuring, inferring, classifying, predicting, communicating as well as observing the social attitude on stage mental and neural state, of readiness to respond, organized, through experience, and exerting a directive (b) science process skills is not observed from the behavior of learners assessed by working the worksheet (c) the self-assessment of social attitudes among learners friends used only at the stage of evaluate; (2) the instrument has been developed fit for use because it meets the content validity by experts and reliability was good value. (3) Results of measurement using observation sheet science process skills get a very good category and the results of measuring social attitude of learners using observation sheets, self-assessment and peer assessment obtained either category on aspects of mental and neural state, of readiness to respond, organized, through experience, and exerting a directive .